Uji Aktivitas dan Karakteristik Kombucha Sari Buah Markisa (Passiflora edulis Sims) Terhadap Bakteri Escherichia coli dan Bacillus subtilis Secara In Vitro - Salsabila, Qothrunnada Shafa; Mayasari, Ulfayani; Selvia, Irda Nila (PendIPA Journal of Science Education, 2024)
Fermented drinks are drinks that due to the fermentation process produce lactic acid bacteria (LAB) which are good for human digestion. Kombucha is a fermented drink produced from the symbiosis between bacteria and yeast known as SCOBY (Symbiotic Culture Bacteria & Yeast). This study aims to determine the characteristics and antibacterial activity of passion fruit kombucha (Passiflora edulis Sims) against the growth of Escherichia coli and Bacillus subtilis bacteria in vitro. The method used in the antibacterial activity test uses the disc diffusion method with concentrations of 20%, 30%, 40% and 50%. This study shows the antibacterial activity of passion fruit kombucha (Passiflora edulis Sims) using concentrations of 20%, 30%, 40% and 50% with the results of the inhibition zone diameter of Escherichia coli bacteria of 10.4 mm, 12.3 mm, 14.2 mm, and 16.3 mm. While Bacillus subtilis bacteria are 14.5 mm, 16.6 mm, 17.8 mm and 18.3 mm. The characteristics of passion fruit kombucha juice have a pH value that is increasingly acidic when the concentration given is higher. Concentrations of 20%, 30%, 40% and 50% have a distinctive kombucha aroma and are golden yellow in color. Concentrations of 40% and 50% have a sour taste. Based on an average concentration of 50% on Escherichia coli bacteria and a concentration of 30% on Bacillus subtilis bacteria, it has effective inhibitory power in inhibiting bacteria.